2021
DOI: 10.1111/bjhp.12501
|View full text |Cite
|
Sign up to set email alerts
|

What makes one feel eustress or distress in quarantine? An analysis from conservation of resources (COR) theory

Abstract: Objective. Health quarantines produce serious deterioration in psychological health, which becomes more affected the longer the quarantine lasts. According to the Conservation of Resources theory from Hobfoll (1989, American Psychologist, 44, 513), those people who have a good supply of resources will be able to cope better with the adversities and will show less distress. The objective of this research is to identify what are the resources that, in a situation of confinement under the threat of COVID-19, pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 38 publications
2
19
0
4
Order By: Relevance
“…According to the Conservation of Resources theory (Hobfoll, 1989), employees who perceive a good supply of resources will identify better strategies to cope with the adversities of working from home and have less stress. A study developed by Merino et al (2021) revealed that the level of stress is dependent upon variables of employment situation, work satisfaction, and the time employees devote to work, as well as the amount of space available in the home and interference from children or other persons there.…”
Section: The New (Ab)normal Context -Implications For Home and Work Lifementioning
confidence: 99%
“…According to the Conservation of Resources theory (Hobfoll, 1989), employees who perceive a good supply of resources will identify better strategies to cope with the adversities of working from home and have less stress. A study developed by Merino et al (2021) revealed that the level of stress is dependent upon variables of employment situation, work satisfaction, and the time employees devote to work, as well as the amount of space available in the home and interference from children or other persons there.…”
Section: The New (Ab)normal Context -Implications For Home and Work Lifementioning
confidence: 99%
“…However, acquisition and conservation of resources and linked with eustress. It is, therefore, pertinent to identify and retain employees' resources so that they cope up with catastrophic or any other kind of occupational stress in a healthier way(M. D. Merino et al, 2021). Knowledge Sharing Behaviour (KSB) is "a set of individual behaviours concerning sharing one's job-related knowledge and expertise with colleagues" (Yi, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, this study focuses on the personal, condition, and energy resources and their impact on Tacit Knowledge Sharing Behaviour (TKSB), with COVID-Induced Occupational Stress (CIOS) moderation. M. D. Merino, Vallellano, Oliver, and Mateo (2021) claimed that researchers earlier studied COR theory in the Turkey earthquake, hurricane Katrina, Taiwan towers attack, but no one applied it in the COVID-19 context. They further found that when there is fear of loss of resources or lack of gain, there will be a lack of adaptation to the changing environment, which results in distress.…”
mentioning
confidence: 99%
“…Although there are numerous scales for the assessment of distress (amongst others, the widely used Perceived Stress Scale by Cohen et al [ 17 ]), eustress has not received enough attention in terms of operationalization and measurement. In a recent paper, Merino et al [ 18 ] used positive and negative affect experienced in relation to COVID-19 quarantine as indicators of eustress and distress, respectively. The COVID-19 pandemic is indeed a global stressor [ 19 , 20 , 21 , 22 ] that can trigger either eustress or distress in the population [ 20 , 23 ].…”
Section: Introductionmentioning
confidence: 99%